Sustainable alternatives to dietary fish oil in tropical fish aquaculture - Ramez Alhazzaa; Peter D. Nichols; Chris G. Carter (Reviews in Aquaculture, 2019)
Marine tropical carnivorous (MTC) fish are less tolerant to high dietary lipid compared with cold and temperate climate fish. However, insufficient n‐3 long‐chain (≥C 20 ) polyunsaturated fatty acids (LC‐PUFA) compromises MTC fish health and growth which requires attention when choosing lipid sources in aquafeed formulations. Fish oil (FO) has been the major lipid source for feeding key MTC fish. We estimated that more than 200 thousand tonnes of FO were used to feed farmed MTC fish in 2016, representing nearly 25% of global FO production. Nevertheless, recent increases in FO prices and demand, and the foreseen inability of wild fisheries to produce sufficient FO in the future, have created a need for cheaper and more sustainable alternatives. Meta‐analysis showed that feeding vegetable oils (VO) to MTC fish can slightly reduce their growth, with a marked decrease in n‐3 LC‐PUFA content in the fish tissues corresponding with the increased replacement of FO and fishmeal in the diet. Rendered terrestrial animal fat or modulating the bioconversion of n‐3 LC‐PUFA precursors in VO can be utilised further in MTC fish nutrition with more research recommended on these approaches. Oils and oil‐rich meals from non‐food marine organisms are rich in n‐3 LC‐PUFA and represent an underutilised alternative to FO for tropical aquaculture. With oils rich in n‐3 LC‐PUFA produced from transgenic plants presently gaining regulatory approvals and becoming available as a renewable alternative to FO, aquaculture in the tropics and around the globe is ready to leap into a new phase of sustainable expansion.